Elf pets : a reindeer tradition - Bell, Chanda A. (Atlanta, Georgia : Creatively Classic Activities and Books, 2014)
The scout elves have reindeer pets who must use the Christmas magic in their hearts to help Santa's sleigh fly on Christmas Eve.
Keywords: Elves -- Juvenile fiction; Reindeer -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Christmas stories